Periodontal Disease in the Brazilian Population: A Retrospective Analysis on the 2013 National Health Survey to Identifying Risk Profiles - Thiago Antônio Raulino do Nascimento; José Vilton Costa; Ricardo Oliveira Guerra (International Journal of Dentistry)
Periodontal disease (PD) is a global public health problem with prevalence varying according to social and economic contexts; however, few studies have investigated the distribution of PD worldwide. PD is the host response to an infection or progression of a clinical condition, and the identification of modifiable risk factors for adequate clinical management of patients should be a priority in health policies directed to vulnerable population groups. In this context, we investigated the characteristics and risk factors for PD using the Brazilian National Health Survey 2013 (PNS-2013). A cluster analysis using the interdependence technique was applied to explore data on the risk of periodontitis. The presence or absence of a risk factor was analyzed using five variables (ten categories), while ordinal regression assessed risk profiles based on sociodemographic aspects of the Brazilian population. Individuals were classified as low (26.33%), medium (23.34%), or high risk (50.32%) for PD. Age, educational level, ethnicity, and Brazilian regions (except the North region) were significantly associated with risk for PD in the adjusted final regression model. Individual and social contexts were factors related to the high risk of PD in the Brazilian population. Our results highlight the need for public policies on healthy habits to prevent systemic diseases affecting oral health.